2022
DOI: 10.1371/journal.pone.0276293
|View full text |Cite
|
Sign up to set email alerts
|

Oral mitis group streptococci reduce infectivity of influenza A virus via acidification and H2O2 production

Abstract: Members of the mitis group streptococci are the most abundant inhabitants of the oral cavity and dental plaque. Influenza A virus (IAV), the causative agent of influenza, infects the upper respiratory tract, and co-infection with Streptococcus pneumoniae is a major cause of morbidity during influenza epidemics. S. pneumoniae is a member of mitis group streptococci and shares many features with oral mitis group streptococci. In this study, we investigated the effect of viable Streptococcus oralis, a representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Therefore, considering the reduction of NA-producing bacterial flora through the improvement of oral hygiene might be a valuable approach to mitigate the risk of influenza pneumonia, as well as secondary bacterial pneumonia. On the other hand, we recently reported that S. oralis is capable of inactivating IAV through the production of short-chain fatty acids and hydrogen peroxide [71] . It appears that the synergistic mechanisms through which the oral bacterial flora can influence respiratory diseases, including influenza infection, are complex and multifactorial, simultaneously influenced by factors related to the oral environment, host, viral, and bacterial factors.…”
Section: Interaction Between Oral Bacterial Flora and Viral Infectionmentioning
confidence: 98%
“…Therefore, considering the reduction of NA-producing bacterial flora through the improvement of oral hygiene might be a valuable approach to mitigate the risk of influenza pneumonia, as well as secondary bacterial pneumonia. On the other hand, we recently reported that S. oralis is capable of inactivating IAV through the production of short-chain fatty acids and hydrogen peroxide [71] . It appears that the synergistic mechanisms through which the oral bacterial flora can influence respiratory diseases, including influenza infection, are complex and multifactorial, simultaneously influenced by factors related to the oral environment, host, viral, and bacterial factors.…”
Section: Interaction Between Oral Bacterial Flora and Viral Infectionmentioning
confidence: 98%
“…Body of knowledge S. oralis is part of the normal microbiota of the oropharyngeal, nasal, gastrointestinal and genitourinary tracts and has a 'probiotic' effect providing protection against invading pathogens in the oral cavity (reviewed by Okahashi et al, 2022a;Bidossi et al, 2018). Strains of this species are used as oral 'probiotics', but strains of the same species are responsible for human infections.…”
Section: Identitymentioning
confidence: 99%